Sex Differences in Nonculprit Coronary Plaque Microstructures on Frequency-Domain Optical Coherence Tomography in Acute Coronary Syndromes and Stable Coronary Artery Disease. (August 2016) - Kataoka, Yu; Puri, Rishi; Hammadah, Muhammad; Duggal, Bhanu; Uno, Kiyoko; Kapadia, Samir R.; Tuzcu, E. Murat; Nissen, Steven E.; King, Peta; Nicholls, Stephen J.
Abstract : Background—: Numerous reports suggest sex-related differences in atherosclerosis. Frequency-domain optical coherence tomography has enabled visualization of plaque microstructures associated with disease instability. The prevalence of plaque microstructures between sexes has not been characterized. We investigated sex differences in plaque features in patients with coronary artery disease. Methods and Results—: Nonculprit plaques on frequency-domain optical coherence tomography imaging were compared between men and women with either stable coronary artery disease (n=320) or acute coronary syndromes (n=115). A greater prevalence of cardiovascular risk factors was observed in women. Nonculprit plaques in women with stable coronary artery disease were more likely to exhibit plaque erosion (8.6% versus 0.3%; P =0.03) and a smaller lipid arc (163.1±71.4° versus 211.2±71.2°; P =0.03), and less likely to harbor cholesterol crystals (17.2% versus 27.5%; P =0.01) and calcification (15.4% versus 34.4%; P =0.008), whereas fibrous cap thickness (105.2±62.1 versus 96.1±40.4 µm; P =0.57), the prevalence of thin-cap fibroatheroma (26.5% versus 25.2%; P =0.85), and microchannels (19.2% versus 20.5%; P =0.95) were comparable. In women with acute coronary syndrome, a smaller lipid arc (171.6±53.2° versus 235.8±86.4°; P =0.03), a higher frequency of plaque erosion (11.4% versus 0.6%; P =0.04), and a lower prevalence of cholesterol crystal (28.6% versus 38.2%; P =0.03) and calcification (10.0% versus 23.7%; P =0.01) were observed. These differences persisted after adjusting clinical demographics. Although thin-cap fibroatheromas in men clustered within proximal arterial segments, thin-cap fibroatheromas were evenly distributed in women. Conclusions—: Despite more comorbid risk factors in women, their nonculprit plaques exhibited more plaque erosion, and less cholesterol and calcium content. This distinct phenotype suggests sex-related differences in the pathophysiology of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.